Dysregulated lipid metabolism mediates the association between brominated flame retardant exposure and hyperuricemia: Evidence from NHANES 2003–2004 - Wang, Yiqian; Wang, Xianhao; Yan, Yingqi; Zhao, Zihui; Yan, Ruxu; Zhang, Yuming; Liu, Meng; Yue, Xianfeng; Wu, Qingqing; Ma, Xin; Jiang, Hongchen; Ji, Long; et al. (Ecotoxicology and environmental safety, 2025)
Brominated flame retardants (BFRs) represent a group of synthetic chemical compounds that have been ubiquitously incorporated into numerous consumer products. Human exposure to BFRs occurs through multiple routes, posing potential health risks. However, the association between BFR exposure and hyperuricemia and the role of lipid dysregulation remain unexplored. Data from 1171 respondents to the National Health and Nutrition Examination Survey (NHANES) survey cycle of 2003–2004 were used. We investigated the risk of hyperuricemia (HUA) from mixed BFR exposure using weighted quantile sum (WQS), quantile g-computation (Qgcomp), Bayesian kernel machine regression (BKMR), Elastic Net (ENET), and decision tree classifier (DT) models. The models were interpreted using Shapley Additive exPlanations (SHAP). Our results indicate that the weights of BDE-28, BDE-47, and BDE-99 are higher than those of the other BFR congeners analyzed. Total cholesterol (TC) was found to mediate the effects of BDE-28, BDE-47, and BDE-99 on hyperuricemia, with mediation proportions of 10.11 %, 10.10 %, and 9.55 %, respectively. Functional enrichment analyses revealed significant enrichment in lipid and atherosclerosis pathways. According to our findings, exposure to BFRs fosters hyperuricemia, and dysregulated lipid metabolism is a major contributing factor to this relationship. [Display omitted] ●Brominated flame retardant (BFR) exposure are positively linked to hyperuricemia.●BDE-28, BDE-47 and BDE-99 are key factors between BFR exposure and hyperuricemia.●Total cholesterol plays a mediating role between BFR exposure and hyperuricemia.●BFRs affect hyperuricemia mainly through lipid and atherosclerosis pathways.